Active music therapy approach in amyotrophic lateral sclerosis: a randomized-controlled trial. Issue 4 (December 2016) - Raglio, Alfredo; Giovanazzi, Elena; Pain, Debora; Baiardi, Paola; Imbriani, Chiara; Imbriani, Marcello; Mora, Gabriele
Abstract : This randomized controlled study assessed the efficacy of active music therapy (AMT) on anxiety, depression, and quality of life in amyotrophic lateral sclerosis (ALS). Communication and relationship during AMT treatment were also evaluated. Thirty patients were assigned randomly to experimental [AMT plus standard of care (SC)] or control (SC) groups. AMT consisted of 12 sessions (three times a week), whereas the SC treatment was based on physical and speech rehabilitation sessions, occupational therapy, and psychological support. ALS Functional Rating Scale-Revised, Hospital Anxiety and Depression Scale, McGill Quality of Life Questionnaire, and Music Therapy Rating Scale were administered to assess functional, psychological, and music therapy outcomes. The AMT group improved significantly in McGill Quality of Life Questionnaire global scores ( P =0.035) and showed a positive trend in nonverbal and sonorous-music relationship during the treatment. Further studies involving larger samples in a longer AMT intervention are needed to confirm the effectiveness of this approach in ALS.